CO₂ reactor-curing for early-strength MgO-based cementitious systems - Gonzalo Mármol; Inés García-Lodeiro (Case Studies in Construction Materials)
This study investigates the development of Mg-based cementitious systems through CO₂-reactor curing, optimizing their application in prefabricated construction materials with enhanced early-age strength. It examines the role of SiO₂ in promoting magnesium silicate hydrate (M-S-H) gel formation and its interaction with carbonation curing. MgO and M-S-H cement pastes were exposed to pressurized CO₂ curing (8.5 bar, 55 °C) with varying water-to-cement ratios to control porosity and carbonation kinetics. FTIR and XRD analyses confirmed that carbonation alters the hydration pathway, promoting brucite transformation into amorphous and crystalline magnesium carbonates. TGA and NMR results revealed that carbonation disrupts the silicate network, limiting M-S-H formation and leaving unreacted SiO₂. Microscopic characterization (SEM/TEM) showed brucite dissolution followed by nucleation of poorly crystalline carbonates, exhibiting hybrid features of nesquehonite and hydromagnesite. Mechanical testing demonstrated that CO₂ curing significantly improves compressive strength, particularly in 100 % MgO systems with higher water-to-cement ratios and in M-S-H systems within the first 24 h. These findings highlight carbonation curing as an effective method to accelerate strength development in Mg-based cements, enhancing their suitability for prefabricated applications. Additionally, the study provides new insights into the limited reactivity of SiO₂ under carbonation, suggesting alternative strategies for optimizing M-S-H formation. This work advances the understanding of Mg-based cement chemistry under CO₂ curing, paving the way for sustainable, high-performance construction materials.